2020
DOI: 10.3390/molecules25040834
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetland Revealed Efficient Sulfamethoxazole Removal but Enhanced the Spread of Antibiotic Resistance Genes

Abstract: Constructed wetlands (CWs) could achieve high removal efficiency of antibiotics, but probably stimulate the spread of antibiotic resistance genes (ARGs). In this study, four CWs were established to treat synthetic wastewater containing sulfamethoxazole (SMX). SMX elimination efficiencies, SMX degradation mechanisms, dynamic fates of ARGs, and bacterial communities were evaluated during the treatment period (360 day). Throughout the whole study, the concentration of SMX in the effluent gradually increased (p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The long residence time of antibiotics or metals subjected to heterogeneous conditions within the CWs, along with the presence of other stressors, can also promote the microorganism's antibiotic resistance by selective pressure [117,118]. Zhang et al (2020) reported about the increase of sulfonamide resistance genes, as well as the increase of sulfamethoxazole concentration in the lower and the medium layers of the CWs [119]. On the contrary, Fang et al (2017) analyzed the removal efficiencies of 14 ARGs (sul1, sul2, sul3, tetA, tetB, tetC, tetE, tetH, tetM, tetO, tetW, qnrB, qnrS, and qepA), intI1, and 16S rRNA genes in an integrated surface flow CW divided in four different subsystems [111].…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…The long residence time of antibiotics or metals subjected to heterogeneous conditions within the CWs, along with the presence of other stressors, can also promote the microorganism's antibiotic resistance by selective pressure [117,118]. Zhang et al (2020) reported about the increase of sulfonamide resistance genes, as well as the increase of sulfamethoxazole concentration in the lower and the medium layers of the CWs [119]. On the contrary, Fang et al (2017) analyzed the removal efficiencies of 14 ARGs (sul1, sul2, sul3, tetA, tetB, tetC, tetE, tetH, tetM, tetO, tetW, qnrB, qnrS, and qepA), intI1, and 16S rRNA genes in an integrated surface flow CW divided in four different subsystems [111].…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…As a nature-based solution, constructed wetlands (CWs) have been used for various types of wastewater treatment [9][10][11], and are able to play the role of the last barrier for antibiotic treatment before entering into natural systems [12,13]. Previous studies have reported that CWs could effectively remove various antibiotics, such as tetracyclines [14], sulfonamides [15], quinolones [16], ibuprofen [17], and macrolides [18], with the removal efficiencies in the range of 75.8~98.6%, through the mechanisms of adsorption, plant uptake, and biodegradation. In order to enhance and secure a sustainable effective treatment performance, further intensification approaches to CWs need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of antibiotics and ARGs in CWs, as demonstrated, could be achieved at relatively similar or even higher rates than in conventional WWTPs [ 36 ]. On the other hand, it was also suggested that, although CWs effectively remove antibiotics, they probably stimulate the spread of ARGs [ 41 ].…”
Section: Introductionmentioning
confidence: 99%